Lean manufacturing in Indian context: A survey - Rakesh Kumar; Vikas Kumar (Management Science Letters)
This paper is an attempt to examine the implementation of Lean Manufacturing system in the Indian industries. Predominant elements of Lean Manufacturing, benefits gained after its implementation and obstacles observed by Indian Industry have been recognized. The results of this survey support the opinion that Lean Manufacturing had potential to improve the organizational performance of Indian industries. Nevertheless, Indian industries are required to be passionate to transform their manufacturing by adopting Lean manufacturing to gain the full benefits. A large numbers of literature papers are available on the better side of Lean manufacturing approach and its benefits gained by manufacturing organizations after implementation. But the adverse impacts of Lean manufacturing are not discussed to a great extent. Some drawbacks of Lean manufacturing are also highlighted in this paper.